2003
DOI: 10.1002/ps.810
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal effects of neem (Azadirachta indica) extracts on edible tropical land snails

Abstract: The effects of 350, 500 and 700 mg kg(-1) of crude extracts of neem, Azadirachta indica A Juss, on edible tropical land snails Archachatina marginata and Limicolaria aurora (Jay) were determined and compared with control using pawpaw, Carica papaya L as bait. Responses were measured through normal feeding, cessation of food intake, cessation of crawling, mucus secretion, lack of response to mechanical stimuli (mortality) and decomposition. Results showed no effects on the controls or snails exposed to neem see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…Reports of Pawert et al (1996) studying collembolan indicated comparatively high tolerance, which were also reflected by its remarkably low mortality during exposure. Contrary to studies of Ebenso (2004), no neurotoxic effects were observed in the present study. Neurotoxic effects may result in alteration in feeding behaviour (Bailey 1989).…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…Reports of Pawert et al (1996) studying collembolan indicated comparatively high tolerance, which were also reflected by its remarkably low mortality during exposure. Contrary to studies of Ebenso (2004), no neurotoxic effects were observed in the present study. Neurotoxic effects may result in alteration in feeding behaviour (Bailey 1989).…”
Section: Resultscontrasting
confidence: 56%
“…In the laboratory studies, mostly an artificial type of food was used (Gomot-de Vaufleury and Kerhoas 2000). Contaminants are taken up by snails through diet, which serve both as food and bait (Ebenso 2004). Besides, elevated metal concentrations in the food can directly influence consumption, growth, reproduction and survival (Russell et al 1981).…”
mentioning
confidence: 99%
“…Using criteria such as feed intake, cessation of crawling, mucus secretion, lack of response to mechanical stimuli, decomposition (Ebenso 2004) and even enzyme profiles (Rao et al 2003), the molluscidal effect of A. indica products on several species and sub-species of snails has been evaluated.…”
Section: Molluscidal Effectsmentioning
confidence: 99%
“…P. canaliculata was more sensible to ethanol exposure than observed for the snails Archachatina marginata and Limicoloria aurora exposed to Azadirachta indica (40 and 60% mortality on 700 mg Kg -1 exposure, respectively) (Ebenso, 2003). (Florêncio et al, 2014).…”
Section: Resultsmentioning
confidence: 97%